A method to include life cycle assessment results in choosing by advantage (Cba) multicriteria decision analysis. a case study for seismic retrofit in peruvian primary schools - Vázquez-Rowe, I.; Córdova-Arias, C.; Brioso, X.; Santa-Cruz, S. (MDPI, 2021)
Building information modeling (BIM) is an emerging technology that improves visualization, understanding, and transparency in construction projects. Its use in Latin America and the Caribbean (LA&C), while still scarce, is developing in combination with multi-criteria decision-making (MCDM) methods, such as the choosing by advantages (CBA) method. Despite the holistic nature of MCDM methods, the inclusion of life cycle environmental metrics is lagging in construction projects in LA&C. However, recent studies point toward the need to optimize the synergies between BIM and life cycle assessment (LCA), in which a method like CBA could allow improving the quality of the decisions. Therefore, the main objective of this study is to integrate LCA and CBA methods to identify the effect that the inclusion of environmental impacts can have on decision-making in public procurement, as well as comparing how this final decision differs from an exclusively LCA-oriented interpretation of the results. Once the LCA was performed, a set of additional criteria for the CBA method were fixed, including transparency, technical, and social indicators. Thereafter, a stakeholder participative workshop was held in order to gather experts to elucidate on the final decision. The methodology was applied to a relevant construction sector problem modelled with BIM in the city of Lima (Peru), which consisted of three different construction techniques needed to retrofit educational institutions. Results from the LCA-oriented assessment, which was supported by Monte Carlo simulation, revealed a situation in which the masonry-based technique showed significantly lower environmental impacts than the remaining two options. However, when a wider range of technical, social, and transparency criteria are added to the environmental indicators, this low-carbon technique only prevailed in those workshop tables in which environmental experts were present and under specific computational assumptions, whereas teams with a higher proportion of government members were inclined to foster alternatives that imply less bureaucratic barriers. Finally, the results constitute an important milestone when it comes to including environmental factors in public procurement in LA&C.
Keywords: Building information modeling; Life cycle assessment; Choosing by advantages; https://purl.org/pe-repo/ocde/ford#2.01.00